Cadernos do Ceis 20 N.º 28: Tendências no ensino da História na educação não superior: o lugar da História no currículo e na formação dos estudantes em Portugal, Espanha, França e Inglaterra - Sara Dias-Trindade (Cadernos do Ceis20, 2019)
Throughout this book, an analysis is made of how History teaching is organized in what the International Standard Classification of Education standards call Secondary Education (ISCED 2 and 3), in four different European countries, in order to compare the importance given to History, the type of curriculum chosen and its place in the Secondary Education. In addition to Portugal, the other three countries (Spain, France and England) were chosen because of the historical relation each one has with Portugal. Considered fundamental in the integral formation of any young person and important for the development of critical thinking, it is possible to withdraw from the analysis carried out the idea that despite the importance that is notoriously given to this subject, there have been many debates regarding what to teach and also its general purpose in Education.